Effects of probiotics application on the hatchery culture of blue swimming crab, Portunus pelagius (Linnaeus, 1758) - Alvarez, Gelene Roda I. (Miagao,Iloilo University of the Philippines in the Visayas, 2020)
A series of experiments were conducted to evaluate the efficacy of Micrococcus luteus, Streptococcus porcinus, Staphyloccocus aureus and their combination as probiotics for the blue swimming crab, Portunus pelagicus larvae. The first experiment compared the inhibitory activities of these probiotics against Vibrio harveyi and V. parahaemolyticus in-vitro. The test probiotics at a density of 109 CFUml-1 were applied on a lawn of Vibrio in solid plate media and the resulting inhibitory zones were quantified. Results showed that all probiotics were inhibitory against these Vibrios, with the combined probiotics exhibiting the highest activity. The second experiment determined the optimum dose of the best probiotic in the larva; rearing of P. pelagicus. In this trial, different doses of probiotics at 103 (T3), 106 (T2) and 109 (T1) CFU ml-1 were tested. The treatment applied with 10 mg L-1 oxytetracycline served as the positive control group (T4) while the negative control group (T5) received no probiotics. Each treatment was run in triplicates and the experiment was terminated when the larvae reached the megalopa stage. The highest survival was observed inT2. Digestive enzyme analyses showed that lipase and amylase activities were not affected by the probiotic application. In the third experiment, the optimum probiotic dose was tested in a large scale rearing of P. pelagicus larvae. The results showed that probiotic application elicited a 2-fold improvement of survival as compared to the both positive and negative control treatments. The improvement in survival was associated with decreased total microbial and Vibrio loads in the culture water and in the alrvae. The results of this study suggest that the application of mixed species probiotics composed of M. luterus, Streptococcus porcinus and Staphylococcus aureus at a dose of 106 CFU.ml-1 can effectively inhibit the growth of V. harveyi and V. parahaemolyticus and enhance the survival of P. pelagicus larvae in the hatchery.
Thesis (M.S. Fisheries-Aquaculture) - Miagao, Iloilo : CFOS, University of the Philippines Visayas, June 2020..
Keywords: Probiotics